Gambaran Radiografi Tuberkulosis Paru Multidrug-Resistant: Studi Retrospektif di Rumah Sakit Umum Dr. Soetomo Surabaya : [Chest Imaging in Multidrug-Resistant Pulmonary Tuberculosis: Retrospectif Study in Dr. Soetomo General Hospital Surabaya] - Stephanie Christina Sulaiman; Lulus Handayani; Mohammad Yamin Sunaryo Suwandi; Soedarsono Soedarsono (Jurnal Respirasi, 2018)
Background: Multidrug-resistant pulmonary tuberculosis (MDR-TB) is a major health problem worldwide. Prompt diagnosis is necessary for insuring appropriate therapy to lower morbidity and mortality, as well as to prevent disease transmission. Determination of drug-resistance patterns through microbiological examination is sometimes challenging, especially when the sputum acid-fast bacilli smear is negative. Therefore, it is worthwhile to investigate whether there may be radiographic patterns suggesting MDR-TB infection. The objective of this study was to evaluate the radiographic features of MDR-TB. Methods: From September 2015 to March 2018, 167 patients with microbiologically proven MDR-TB were enrolled in the study. All radiographs were obtained before the patients received MDR-TB chemotherapy regimen. Posterior-anterior chest radiography was performed using digital radiography system (Hitachi Radnext50 500mAs) and retrospectively reviewed as digital raw data. Results: Based on severity category, 60% had severe lesion, 31% had moderate lesion, and only 9% had mild lesion. The most frequently observed findings were ground glass opacity or consolidation, noted in 96% patients, with bilateral lung involvement in 81% patients; fibrosis (95%), cavity (78%; 87% of which were multiple), interstitial opacities (53%), pleural thickening and mediastinal shift (59%). Other radiological findings were calcification (16%), emphysema (13%), lung destruction (12%), atelectasis (10%), nodule (8%), bullae (8%), bronchiectasis (5%), miliary pattern (1%), pleural effusion (25%), pneumothorax (1%), and hilar lymphadenopathy (14%) which predominantly unilateral. Conclusion: The presence of severe pulmonary lesion, ground glass opacity or consolidation with bilateral lung involvement, fibrosis, multiple cavities, interstitial opacities, pleural thickening, and mediastinal shift are the main features of MDR-TB.